Synthesis of high purity -SiC and -Si3N4 from rice hulls - Treviño, B.; Gómez de la Fuente, María Idalia del Consuelo; Colás Ortíz, Rafael (Universidad Autónoma de Nuevo León, 2011)
Silicon carbide and silicon nitride were synthesized from ashes obtained by heating rice hulls at 800ºC for 3 hours in argon. -SiC was produced from the ashes by reheating them at 1400ºC for 8 hours in argon, whereas -Si3N4 was obtained by heating the ashes at temperatures ranging from 1250 to 1400ºC for periods of 3 to 6 hours in a nitrogen rich atmosphere. The products were characterized by infrared spectroscopy, X-ray and scanning electron microscopy. High purity -SiC and -Si3N4 compouds with whisker type morphology were obtained. It was possible to obtain -Si3N4 without -SiC by heating the ashes for 6 hours at 1250ºC